Evaluating Plant Biodiversity in Natural and Semi‑Natural Areas with the Help of Aerial Drones - Dragomir D. SÂNGEORZAN; Ioan ROTAR (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Agriculture, 2020)
In the era of abundant information, wisdom has become a scarce resource. Exploration and measurement of biodiversity yield copious amounts of information fragmented into numerous categories and types, following the pattern of life itself. We aim to review the potential of charting the plant diversity of woodlands, grasslands, marshlands, and other natural and semi-natural areas relevant to conservation by using low-altitude, low-cost, Earth Observation technology, such as small aerial drones, that captures images which can be mapped and analyzed. As this technology is new and quickly evolving, we limited the search to published research between 2012-2019. We have found applications for forestry, agro-forestry, horticulture, grasslands, ecological restoration, and other areas. In terms of technological progress, new hardware components and cameras and new software tools leverage drones’ power to deliver a greater quantity and quality of information. There are promising efforts to develop low-cost drone technology that facilitate better biodiversity conservation results. For analysis, software tools are also improving to take advantage of increases in computing power and artificial intelligence programming. Our findings serve as an introduction to low-cost teledetection for biodiversity conservation, with drones providing an advantage in monitoring habitats by increasing information quantity, accuracy, and ease of analysis with the aid of automation.